Chromosome Architecture and Gene Content of the Emergent Pathogen Acinetobacter haemolyticus - Castro-Jaimes, Semiramis; Bello-López, Elena; Velázquez-Acosta, Consuelo; Volkow-Fernández, Patricia; Lozano-Zarain, Patricia; Castillo-Ramírez, Santiago; Cevallos, Miguel Angel (Frontiers in Microbiology, 2020)
Acinetobacter haemolyticus is a Gammaproteobacterium that has been involved in serious diseases frequently linked to the nosocomial environment. Most of the strains causing such infections are sensitive to a wide variety of antibiotics, but recent reports indicate that this pathogen is acquiring very efficiently carbapenem-resistance determinants like the blaNDM-1 gene, all over the world. With this work we contribute with a collection set of 31 newly sequenced nosocomial A. haemolyticus isolates. Genome analysis of these sequences and others collected from RefSeq indicates that their chromosomes are organized in 12 syntenic blocks that contain most of the core genome genes. These blocks are separated by hypervariable regions that are rich in unique gene families, but also have signals of horizontal gene transfer. Genes involved in virulence or encoding different secretion systems are located inside syntenic regions and have recombination signals. The relative order of the synthetic blocks along the A. haemolyticus chromosome can change, indicating that they have been subject to several kinds of inversions. Genomes of this microorganism show large differences in gene content even if they are in the same clade. Here we also show that A. haemolyticus has an open pan-genome.